Will Sirtuin 2 Be a Promising Target for Neuroinflammatory Disorders? - Fan, Zhang; Bin, Li (Frontiers in Cellular Neuroscience, 2022)
Neuroinflammatory disorder is a general term that is associated with the progressive loss of neuronal structure or function. At present, the widely studied diseases with neuroinflammatory components are mainly divided into neurodegenerative and neuropsychiatric diseases, namely, Alzheimer’s disease, Parkinson’s disease, depression, stroke, and so on. An appropriate neuroinflammatory response can promote brain homeostasis, while excessive neuroinflammation can inhibit neuronal regeneration and damage the central nervous system. Apart from the symptomatic treatment with cholinesterase inhibitors, antidepressants/anxiolytics, and neuroprotective drugs, the treatment of neuroinflammation is a promising therapeutic method. Sirtuins are a host of class III histone deacetylases, that require nicotinamide adenine dinucleotide for their lysine residue deacetylase activity. The role of sirtuin 2 (SIRT2), one of the sirtuins, in modulating senescence, myelin formation, autophagy, and inflammation has been widely studied. SIRT2 is associated with many neuroinflammatory disorders considering it has deacetylation properties, that regulate the entire immune homeostasis. The aim of this review was to summarize the latest progress in regulating the effects of SIRT2 on immune homeostasis in neuroinflammatory disorders. The overall structure and catalytic properties of SIRT2, the selective inhibitors of SIRT2, the relationship between immune homeostasis and SIRT2, and the multitasking role of SIRT2 in several diseases with neuroinflammatory components were discussed.